Characteristics and Dynamics of Full Arch Distalization Using Transpalatal Arches with Midpalatal and Interradicular Miniscrews as Temporary Anchorage Devices: A Preliminary Finite Element Analysis - Mashallah Khanehmasjedi; Sepideh Bagheri; Vahid Rakhshan; Mojtaba Hasani (Hindawi Limited, 2020)
Introduction. Miniscrews have proved quite effective in fixed orthodontic treatment. They can be placed in areas like palatal interradicular zones or midpalatal suture. Despite the value of these methods and their ever-increasing use, their characteristics are not assessed before when implanted in palatal interradicular areas or in the midpalatal suture. We aimed to assess, for the first time, the dynamics of full arch distalization using such miniscrews. Methods. A 3D model of maxilla with all permanent dentition was created from a CT scan volume. Tissues were segmented and differentiated. Afterward, miniscrews and appliances were designed, and the whole model was registered within a finite element analysis software by assigning proper mechanical properties to tissues and orthodontic appliances. The full arches were distalized using transpalatal arches with miniscrews as anchorage devices (in two different models). The extents of stresses and patterns of movements of various elements (teeth, miniscrews, appliances, tissues) were estimated. Results and Conclusions. Comparing the two models, it is obvious that in both models, the stress distribution is the highest in the TPA arms and the head of the miniscrew where the spring is connected. In comparison with the displacement in the X-axis, the "mesial in" rotation is seen in the first molar of both models. But there is one exception and that is the "mesial out" rotation of the right second molar. In all measurements, the amount of movement in Model 2 (with palatal interradicular miniscrews) is more than that in Model 1 (with midpalatal miniscrew). In the Y-axis, more tipping is seen in Model 2, especially the anterior teeth (detorque) and the first molar, but in Model 1, bodily movement of the first molar is more evident. Along the Z-axis, the mesial intrusion of the first molar and the distal extrusion of this tooth can be seen in both models. Again, the displacement values are higher in the second model (with interradicular miniscrews). In comparison with micromotion and stress distribution of miniscrews, in Model 1, maximum stress and micromotion is observed at the head of the miniscrew where it is attached to the spring. Of course, this amount of micromotion increases over time. The same is true for Model 2, but with a lower micromotion. As for the amount of stress, the stress distribution in both miniscrews of both models is almost uniform and rather severe.